Quantitative assessment of heavy metal contamination in lake water using atomic absorption spectrometry - Ali, Rosliza; Marzukhi, Nisa Irdina; Ahmad Zimy, Aisyah Dayini; Mohd Fadzil, Nur Aufa Aliah; Nor Zakuan, Nor Zafirah; Ahmad Syafiq, Nurina Huda; Khairudin, Syasya Syafiah (2025)
This study investigated the concentrations of cadmium (Cd), chromium (Cr), and nickel (Ni) in two freshwater lakes and evaluated their compliance with the Malaysian National Water Quality Standards (NWQS). The analytical procedure was validated using calibration curves with good linearity (R² = 0.984–0.9949). The results revealed severe heavy metal contamination, with all metals exceeding permissible limits. Cadmium concentrations (0.34–0.40 ppm) and nickel concentrations (1.52–1.53 ppm) showed the most dramatic exceedances, surpassing their regulatory thresholds (0.01 ppm and 0.05 ppm, respectively) by more than an order of magnitude. Chromium levels (0.1–0.3 ppm) also consistently breached the safety limit (0.05 ppm), with concentrations 2 to 6 times higher than allowed. The findings confirm a critical level of pollution, with the notably high concentrations of Cd and Ni being of particular concern due to their chronic toxicity and bioaccumulation potential, indicating a substantial risk to aquatic ecosystem integrity and public health.